Anorexia and Cachexia: Multidisciplinary Assessment, Diagnosis, Prevention, and Management Across Nursing, Clinical Nutrition, Physical Therapy, Diagnostic Radiology, Public Health, and Epidemiology - Alotaibi, Mohsen Dughaylib Ghazai; Hamad Hadi Saeed Al-Dughman; Nourah Abdurouf Turki; Abdullah Ateeq Oudah Alsubhi; Abdullah Mohammed Hassan Mindil; Abdulkarim Hadi Othman Hakmi; Mihaf Kamal Alrajhi (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Cachexia is a multifactorial metabolic syndrome associated with chronic diseases, particularly advanced malignancies, chronic obstructive pulmonary disease, heart failure, chronic kidney disease, and chronic infections. It is characterized by progressive skeletal muscle wasting, adipose tissue loss, systemic inflammation, and metabolic dysregulation that cannot be fully reversed by conventional nutritional support. When accompanied by severe appetite loss, it manifests as anorexia-cachexia syndrome, resulting in substantial functional decline and increased mortality. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aimed to provide a comprehensive overview of the etiology, epidemiology, pathophysiology, clinical assessment, diagnostic evaluation, prevention, and multidisciplinary management of anorexia and cachexia while highlighting evidence-based strategies that improve patient outcomes across multiple healthcare disciplines. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative educational review was conducted by synthesizing current evidence, international clinical guidelines, and published literature regarding the mechanisms, diagnosis, nutritional assessment, functional evaluation, and therapeutic management of cachexia in patients with chronic diseases. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Cachexia develops through complex interactions among chronic inflammation, neuroendocrine dysfunction, metabolic abnormalities, and impaired protein synthesis, resulting in progressive muscle wasting and functional deterioration. Early diagnosis requires comprehensive clinical, nutritional, anthropometric, laboratory, and functional assessments. Management is most effective when multidisciplinary, integrating nutritional optimization, individualized exercise programs, pharmacological therapies, psychosocial support, and treatment of the underlying disease. Emerging therapies targeting inflammatory and metabolic pathways show promising potential, although further clinical evidence is needed. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Early recognition and multidisciplinary intervention are essential for slowing disease progression, preserving muscle mass, improving functional capacity, enhancing quality of life, and optimizing clinical outcomes. Comprehensive patient-centered management remains the cornerstone of effective cachexia care.